Discourse and identity - Susana Ridao Rodrigo (Tejuelo: Didáctica de la Lengua y la Literatura)
Reseña BibliográficaAnna de Fina, Deborah Schiffrin y Michael Bamberg (eds.). Discourse and Identity. Cambridge. Cambridge University Press. 2006. 462 págs. ISBN 100-521-54191-3